Studi Karakteristik Kekuatan Tarik Dan Harga Impak Material Polymeric Foam Sandwich Panels Komposit Dengan Variasi Arah Serat Tandan Kosong Sawit, Tekanan Vari, Dan Ketebalan Foam - Erik Johannes Sitio; Muftil Badri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study refers to the study of tensile strength and impact properties of polymeric foam sandwich panels composite material with variations in the direction of empty fruit bunch fiber, VARI pressure, and foam thickness. The results of composite specimen analysis in the study were evaluated and compared with each other. From the test result, it was found that the highest tensile strength was the composite specimen with the direction of the verical fiber ie the specimen with the third vertical fiber direction, the pressure vari 6 cmHg, and the thickness of foam 1.5 mm with tensile strength is 22.5041 ????/????????2, the highest impact price is the specimen with vertical fiber direction ie specimen with three vertical panels fiber direction, pressure vari 6 cm Hg, and thickness foam 1,5 mm with impact price 0,1646 ????/????????2. the direction of the verical fiber is 53% higher than the direction of consecutive, vertical, horizontal and vertical combined fibers in absorbing impact loads, also 83% higher than the combined vertical, 45⁰, and horizontal joint directions in absorbing impact load , also has a tensile strength of 10% higher than the direction of vertical, horizontal and vertical combined fibers, also has a tensile strength of 15% higher than the combined vertical, 45⁰, and horizontal combined directions.Keywords : Polymeric Foam, sandwich panels, empty fruit bunch.